Lipophilic Constituents in Salvia miltiorrhiza Inhibit Activation of the Hepatic Stellate Cells by Suppressing the JAK1/STAT3 Signaling Pathway: A Network Pharmacology Study and Experimental Validation - Tang, Ya-Xin; Liu, Mingming; Liu, Long; Zhen, Bo-Rui; Wang, Tian-Tian; Li, Na; Lv, Nanning; Zhu, Zhenyu; Sun, Guoquan; Wang, Xiaobo; Chen, Si (Frontiers in Pharmacology, 2022)
Liver fibrosis is currently a global health challenge with no approved therapy, with the activation of hepatic stellate cells being a principal factor. Lipophilic constituents in Salvia miltiorrhiza (LS) have been reported to improve liver function and reduce the indicators of liver fibrosis for patients with chronic hepatitis B induced hepatic fibrosis. However, the pharmacological mechanisms of LS on liver fibrosis have not been clarified. In this study, 71 active compounds, 342 potential target proteins and 22 signaling pathways of LS were identified through a network pharmacology strategy. Through text mining and data analysis, the JAK1/STAT3 signaling pathway was representatively selected for further experimental validation. We firstly confirmed the protective effect of LS on liver fibrosis in vivo by animal experiments. Hepatic stellate cells, which proliferated and displayed a fibroblast-like morphology similar to activated primary stellate cells, were applied to evaluate its underlying mechanisms. The results showed that LS could inhibit the cell viability, promote the cell apoptosis, decrease the expression of liver fibrosis markers, and downregulate the JAK1/STAT3 signaling pathway. These results demonstrated that LS could exert anti-liver-fibrosis effects by inhibiting the activation of HSCs and regulating the JAK1/STAT3 signaling pathway, which is expected to benefit its clinical application.